Level of learning from occupational accidents: current status in Malaysia - Kidam, Kamarizan (2015)
The occupational safety and health (OSH) accident rate in Malaysia is decreasing, however, statistically it is still high if compared to the other developing nations. One of the reasons why accidents keep on happening is due to poor learning from accidents. This paper discusses the level of accident learning from accident reports submitted to the Department of Occupational Safety and Health (DOSH) Malaysia and the Society Security Organization (SOCSO) Malaysia involving 1,291 accident cases. Based on the quality and completeness of the accident reports, the levels of learning were ranked using the knowledge management hierarchy. Based on the analysis, the level of learning from accidents among the industries in Malaysia was less than adequate which promotes limited learning from accident.